2019
DOI: 10.1002/tal.1583
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical investigation on seismic behavior of Q690 circular high‐strength concrete‐filled thin‐walled steel tubular columns

Abstract: This paper proposed a new Q690 circular high-strength concrete-filled thin-walled steel tubular (HCFTST) column comprising an ultrahigh-strength steel tube (yield strength f y ≥ 690 MPa). A quasi-static cyclic loading test was conducted to examine the seismic behavior, and the obtained lateral load-displacement hysteresis curves, skeleton curves, and ductility were analyzed in detail. Then, a numerical model based on a nonlinear fiber beam-column element incorporating the modified uniaxial cyclic constitutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Li et al [1] studied the regulation of secondary stress distribution in UHV steel tube tower and its influencing factors through FEA, but the stress values were obtained according to the finite element model of the ideal beam-rod element, and the stresses obtained by theoretical calculations were not accurate enough. The research group of Sun Qing [10][11][12][13][14][15] examined the axial and seismic performance of high-strength circular concrete-filled thin-walled steel tubular columns. Their test results show that using high-strength Q690 steel could significantly contribute to a larger elastoplastic deformation capacity and delay the onset of post-peak behavior, even though a lower ductility capacity was provided.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [1] studied the regulation of secondary stress distribution in UHV steel tube tower and its influencing factors through FEA, but the stress values were obtained according to the finite element model of the ideal beam-rod element, and the stresses obtained by theoretical calculations were not accurate enough. The research group of Sun Qing [10][11][12][13][14][15] examined the axial and seismic performance of high-strength circular concrete-filled thin-walled steel tubular columns. Their test results show that using high-strength Q690 steel could significantly contribute to a larger elastoplastic deformation capacity and delay the onset of post-peak behavior, even though a lower ductility capacity was provided.…”
Section: Introductionmentioning
confidence: 99%
“…The seismic performance of CFST structures was studied with different concrete strength, steel strength, restraint coefficient, axial compression ratio, and diameter-to-thickness ratio as parameters. [3][4][5][6] Fam et al [7] and Ge and Usami [8] studied the seismic performance of CFST specimens under the combined action of axial compression and lateral cyclic loading and concluded that CFST has high strength and good ductility. Varma et al [9] studied the stiffness, strength, ductility, and energy dissipation of high-strength CFST beams and columns with different width thickness ratio, steel yield stress, and axial…”
mentioning
confidence: 99%